Microscopic Colitis and Reproductive Factors Related to Exposure to Estrogens and Progesterone - Bodil Roth; Jonas Manjer; Bodil Ohlsson (AboutScience Srl, 2013)
Microscopic colitis (MC) often debuts around or after menopause and is divided into lymphocytic- and collagenous colitis. The aim of this study was to examine whether factors influencing sex hormone levels differed between subgroups of MC as well as between patients and controls. A self-administered questionnaire about parity was completed which included questions surrounding age at first childbirth, menarche and menopause, the use of oral contraceptives, and hormonal replacement therapy. Patients with lymphocytic colitis had children less often compared to those with collagenous colitis (OR = 0.20, 95% CI = 0.05-0.86), however no differences were observed between patients with persistent or transient disease. Patients were less often older than 15 years of age at menarche (OR = 0.48, 95% CI = 0.26-0.91) and were younger at menopause (OR = 0.30, 95% CI = 0.16-0.56) compared with controls. Thus, no obvious association between factors influencing sex hormone levels and presence of MC could be found.